2021
DOI: 10.3390/info12050201
|View full text |Cite
|
Sign up to set email alerts
|

Combatting Visual Fake News with a Professional Fact-Checking Tool in Education in France, Romania, Spain and Sweden

Abstract: Educational and technical resources are regarded as central in combating disinformation and safeguarding democracy in an era of ‘fake news’. In this study, we investigated whether a professional fact-checking tool could be utilised in curricular activity to make pupils more skilled in determining the credibility of digital news and to inspire them to use digital tools to further their transliteracy and technocognition. In addition, we explored how pupils’ performance and attitudes regarding digital news and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 61 publications
0
11
0
7
Order By: Relevance
“…Insights from this study were a solid basis for an educational design that yielded noteworthy results from using the digital tool in classrooms. Insights from teachers helped us design a cross-national intervention with significant effects on students' attitudes and abilities to fact-check disinformation (Nygren et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Insights from this study were a solid basis for an educational design that yielded noteworthy results from using the digital tool in classrooms. Insights from teachers helped us design a cross-national intervention with significant effects on students' attitudes and abilities to fact-check disinformation (Nygren et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fact-checking has also been studied beyond journalism, specifically its influence on the evaluation of political messages [41], and its effectiveness correcting political misinformation, which has already been the subject of a meta-analysis [42] and a review analysis [43] focused on the US context. The application of professional fact-checking tools and procedures in media literacy in schools is another area of interest [44,45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Zhang et al ( 33 ) revealed that the use of pictures was negatively related to the veracity of rumors. Nonetheless, visuals may not be related to the veracity of the rumors because rumormongers often included pictures or videos that were not associated with the events ( 78 80 ) or used fake pictures or videos ( 48 , 76 , 81 ) as evidence to imitate the practice of news reports.…”
Section: Discussionmentioning
confidence: 99%